IMPLEMENTASI PERATURAN MENTERI SOSIAL NOMOR 1 TAHUN 2018 TENTANG PROGRAM KELUARGA HARAPAN DALAM PEMBERIAN BANTUAN KEPADA MASYARAKAT MISKIN DI DESA BERANCAH KECAMATAN BANTAN - Nurul Fahmi; Khairil Anwar (Bertuah: Journal of Sharia and Islamic Economics, 2020)
PKH " Program Keluarga Harapan " or the family hope program is such a program that provides cash assistances particularly for poor families in order to improve the quality of their human resources which include education, health and social welfare. Originally The PKH program is a program created by the Indonesian Ministry of Social Affairs which is based on the Decree of the Coordinating Minister for Poverty. And This research is aimed at regarding the implementation of the Minister of Social Affairs Regulation No.1 of 2018 concerning the Family Hope Program in Providing assistance to the Poor society Particularly in Berancah Village, Bantan District. And this study also to determine the obstacles of this program in providing all the  assistances. The type of this research is a descriptive qualitative research which used a sociological approach. Additionally, the Data sources of this study were obtained from primary data and secondary data. Moreover, In data collection techniques, researchers used interview and documentation methods. Then the technical data analysis which used in this research is data reduction, data presentation and conclusions. The results of this study indicate that:  firstly, the implementation of the Minister of Social Affairs Regulation No.1 of 2018 concerning the Family Hope Program in Providing assistance to the Poor society Particularly in Berancah Village, Bantan District is running pretty well, it is proven that recipients of PKH education components for elementary, junior and high school categories can buy their children's school supplies. On the other hand, for the health component, namely the category of pregnant women and toddlers, they can have their nutrition fulfilled. Otherwise, for the social welfare component for the elderly and disabled categories, they can be helped to seek treatment and able to make ends meet. Secondly, the obstacles of this program in providing all the assistances are included internal and external factors. Keywords: PKH, Family Hope Program, Poor Community.